Cicero’s De Divinatione in Religious and Historical Perspective - Begemann, Elisabeth (Ciceroniana On Line, 2023)
The article argues that the imperial expansion of the Late Roman Republic is reflected in Cicero’s philosophical texts by example of De divinatione. The expansion of Rome made it necessary to consider what it meant to be Roman and what Roman practices are, especially confronted with other, alien practices that might seem similar. Cicero offers his texts as an admonition to consider religious practices – here: divination – the Romans might encounter in the provinces and how to deal with them, to consider their usefulness while also bearing in mind the latent danger in not doing them right or exceeding the religious need which upholds the pax deorum. Being put in the context of the expanding empire, the article makes sense of the multiple non-Roman examples cited especially in Book 1 of the treatise De divinatione.